Mental health in children and adolescents: vision of the professionals on challenges and possibilities in building up intersectoral networks - Cristiane Kenes Nunes; Agnes Olschowsky; Aline Basso da Silva; Luciane Prado Kantorski; Valéria Cristina Christello Coimbra (Universidade Federal do Rio Grande do Sul, 2019)
Abstract Objective: To analyze the possibilities and challenges in building intersectoral networks in mental health in the professional's view involved in the care for children and adolescents treated at the Child and Adolescent Psychosocial Care Center. Methods: A qualitative, descriptive and exploratory research, held from May to June 2014, performed a town in southern Brazil. Data were collected through semi-structured interviews with 26 workers intersectoral networking and submitted to thematic analysis. Results: The articulation of different services and intersectoral care devices, and challenges to be overcome, the individual treatment plan, social policies that realize the real needs of users, including family and the medical-hegemonic model, were pointed out as possibilities. Conclusion: The care raised to the intersectoral level is a necessity and a way to achieve new perspectives on care and its articulations to consolidate the Child and Adolescent Mental Health policy.